Homocysteine Is Associated With Future Venous Thromboembolism in 2 Prospective Cohorts of Women. Issue 7 (27th May 2021) - Aday, Aaron W.; Duran, Edward K.; Van Denburgh, Martin; Kim, Eunjung; Christen, William G.; Manson, JoAnn E.; Ridker, Paul M; Pradhan, Aruna D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Case-control studies have identified plasma homocysteine as a risk marker for venous thromboembolism (VTE). Prospective data, particularly among women, are sparse. We examined whether plasma homocysteine associates with incident VTE in 2 large prospective cohorts of women. Approach and Results: In the WHS (Women's Health Study), a prospective cohort study of 27 555 women ≥45 years old and free of cardiovascular disease and VTE, we assessed baseline homocysteine concentration along with other thrombotic biomarkers for association with future VTE (n=743), pulmonary embolism (n=363), and deep vein thrombosis (n=545). We used a second cohort of 2672 women (n=102 VTE events) in the WAFACS (Women's Antioxidant and Folic Acid Cardiovascular Study) to corroborate our findings. In age-adjusted analyses, elevated homocysteine, hsCRP (high-sensitivity C-reactive protein), fibrinogen, and sICAM-1 (soluble intercellular adhesion molecule-1) were associated with incident VTE ( P for extreme quartile comparisons and P -trend <0.05). In multivariable models adjusting for body mass index and other traditional VTE risk factors, only the association for homocysteine persisted (HRQ4, 1.31 [95% CI, 1.06–1.63]). Elevated homocysteine levels were associated with unprovoked pulmonary embolism (HRQ4, 2.13 [95% CI, 1.30–3.51]) and deep vein thrombosis (HRQ4, 1.59 [95% CI, 1.05–2.40]) but not provoked events. In WAFACS, elevated homocysteine levels were also associated with VTE events ( P -trend 0.023). Conclusions: Higher plasma homocysteine levels associate with VTE events in 2 cohorts of middle-aged and older women. Among VTE subtypes, homocysteine was associated with unprovoked, but not provoked, events. These data suggest a plausible biological role for homocysteine in the development of VTE. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00000479, NCT00000541.